2022
DOI: 10.21203/rs.3.rs-1621589/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluorescence tagged salivary exosomes as a nano tool in early diagnosis of Parkinson’s disease

Abstract: Parkinson’s disease is generally asymptomatic at earlier stages. The pressing need is for the susceptibility risk biomarkers, that can aid in better diagnosis and therapeutics as well can objectively serve to measure the endpoint of disease progression. The role of exosomes in progression of neurodegenerative diseases is already reported and its cargo could be potent in playing a revolutionary role in biomarker discovery. In our study, the salivary exosomes were efficiently isolated by chemical precipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In another supportive study, increased DJ-1 and α-syn were found in neural-derived exosomes from PD patients [ 130 ]. In the saliva samples from PD [ 131 , 132 ] and AD patients [ 133 ], neuronal salivary exosomes were found to be increased in a similar pattern. This approach could be extended to other neurodegenerative diseases as well [ 62 ].…”
Section: Nanoparticle Tracking Analysis (Nta): An Emerging Platform F...mentioning
confidence: 99%
“…In another supportive study, increased DJ-1 and α-syn were found in neural-derived exosomes from PD patients [ 130 ]. In the saliva samples from PD [ 131 , 132 ] and AD patients [ 133 ], neuronal salivary exosomes were found to be increased in a similar pattern. This approach could be extended to other neurodegenerative diseases as well [ 62 ].…”
Section: Nanoparticle Tracking Analysis (Nta): An Emerging Platform F...mentioning
confidence: 99%